(untitled) (Fiep Bulletin - online, 2013)
In recent years, within the Bachelor of Primary Education with Emphasis in Physical Education, Recreation and Sports, University of Cundinamarca pedagogical approaches have approached the Popular Education to pedagogical practice scenarios for students. This process has led us to understand the role must have a degree in physical education in the current discussion of pedagogy. This paper presents some of the key issues in terms of physical education in the pedagogical debate, we have found in this process.